Separation Algorithm of the Soyuz MS Spacecraft from Nonstabilized International Space Station - Bakulin, V. N.; Bogomolov, N. V.; Borzykh, S. V. (Russian aeronautics, 2019)
We propose an easy-to-implement algorithm providing the safe (collision-free) separation of the Soyuz MS crew transfer vehicle from the ports of the Rassvet (MRM-1) and Poisk (MRM-2) mini-research modules of the International Space Station at an arbitrary station attitude at the time of separation and angular velocities exceeding the maximum permissible for the current undocking algorithm. A criterion of collision-free separation process is described and a comprehensive mathematical model used for calculation is presented.